The novel methods to enhance the SMA/PLA interfacial strength and in-situ heal the interfacial damage. (October 2021) - Hu, Wenlong; Yang, Bin; Tan, Jianping; Fu, Kunkun; Yuan, Yiwen; Cang, Yu; Li, Yan
Abstracts: This work seeks to develop the effective approaches to enhance the interfacial strength and in-situ heal the interfacial damages in shape memory alloy (SMA) wire reinforced polylactic acid (PLA) matrix. To enhance the interfacial shear strength (IFSS) of SMA/PLA, SMA wires are firstly polished by sandpapers with various meshes, and then treated by acid immersion. The IFSS is evaluated by fiber pull-out test, and SMA diameter/embedded depth effects on the IFSS of the pristine and treated specimens are discussed. Interfacial electrothermal generated by the electrode and conducted through SMA is adopted as a route to in-situ heal the SMA/PLA interfacial damage. The experimental results indicate that IFSS of 1000 mesh polished and acid immersion SMA wire reinforced PLA matrix is the highest. For the modified interface with SMA wire embedded depth of 8 mm, a 100% IFSS recover ratio is obtained after healed for 40s at power of 20W. The purposed method can be utilized to help to design and manufacture the SMA/PLA interface with higher structural and functional abilities in smart structures. Highlights: SMA/PLA with enhanced interfacial strength and in-situ healing ability was obtained. SMA after polished by 1000 mesh sandpapers and acid treated for 45 min has the optimal IFSS with PLA. A 100% IFSS recover ratio was obtained after healed for 40s at power of 20W.